Universal Access in Human-Computer Interaction: Design and Development Methods for Universal Access 8th International Conference, UAHCI 2014, Held as Part of HCI International 2014, Heraklion, Crete, Greece, June 22-27, 2014, Proceedings, Part I - Stephanidis, Constantine.; Stephanidis, Constantine.; Antona, Margherita.; Antona, Margherita. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2014)
The four-volume set LNCS 8513-8516 constitutes the refereed proceedings of the 8th International Conference on Universal Access in Human-Computer Interaction, UAHCI 2014, held as part of the 16th International Conference on Human-Computer Interaction, HCII 2014, held in Heraklion, Crete, Greece in June 2014, jointly with 14 other thematically similar conferences. The total of 1476 papers and 220 posters presented at the HCII 2014 conferences was carefully reviewed and selected from 4766 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The total of 251 contributions included in the UAHCI proceedings were carefully reviewed and selected for inclusion in this four-volume set. The 51 papers included in this volume are organized in the following topical sections: design for all methods, techniques, and tools; development methods and tools for universal access; user models, adaption and personalization; natural, multimodal and multisensory interaction and brain-computer interfaces.